The uplift rate of Sulawesi East Arm and the activity of Batui Fault using a tectonic geomorphology approach in the Luwuk Area, Sulawesi - Hikmy, Isbram Ginanjar; Rudyawan, Alfend; Putri, Berta Syafira; Sapiie, Benyamin; Gunawan, Indra (Jurnal Geologi dan Sumberdaya Mineral, 2025)
Sulawesi is a tectonically active area with convergent triple-junction amidst Eurasian, Indo-Australian and Pacific Plate. The study area is located in the suture zone of sedimentary Banggai-Sula Microcontinent and East Sulawesi Ophiolite. This research is aimed to determine fault activity and rate of tectonic uplift of Luwuk mountainous area. Field geological mapping had been done to determine lithology and geological structure along with morphometric analysis to measure definitive result of tectonic activities. Geological structure features which encountered in this area are Batui Thrust, Pasini Thrust, Lobu Balongan Fault Zone, and Lambangan Anticline. The sedimentary rocks have average N315oE dip direction with angle of 41o. Based on tectonic geomorphology and morphometric analyses are resulting the most active tectonic areas passed by the Batui and Pasini Thrust which have NE-SW direction and Lobu Balolang Fault Zone relative to others. The Batui Thrust is considered as active fault intersected the East Sulawesi Ophiolite and Banggai-Sula Microcontinent which segmented with wrench faults. Number of thrust faults parallel to the Batui Thrust generate Batui Thrust Belt which propagate from the ultramafic rocks to the sedimentary rocks within the suture zone. As a result, the presence of active fault is uplifting the East Arm of Sulawesi with 0.408 ± 0.008 mm and 0.213 ± 0.046 mm uplift rate per year by the presence of high altitude Celebes Molasses. These rates are getting higher to the west. Keywords: Batui Thrust, East Sulawesi Ophiolite, Luwuk, morphometry, tectonic geomorphology, uplift rate